Selective Imaging of the Angiogenic Relevant Integrins α5β1 and αvβ31. Issue 44 (20th September 2013) - Neubauer, Stefanie; Rechenmacher, Florian; Beer, Ambros J.; Curnis, Flavio; Pohle, Karolin; D'Alessandria, Calogero; Wester, Hans‐Jürgen; Reuning, Ute; Corti, Angelo; Schwaiger, Markus; Kessler, Horst
<x xml:space="preserve">Abstract</x> Pattern seekers: For the two angiogenic relevant integrins α5β1 and αvβ3, functionalized derivatives of the selective antagonists 1 and 2 could target and discriminate between tumor cells in vivo based on their different integrin patterns and also delay tumor growth in vivo. In addition, the first α5β1‐selective integrin antagonist that enables specific molecular imaging by positron emission tomography was developed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>